Dynamics analysis of a novel in-wheel powertrain system combined with dynamic vibration absorber. (February 2021) - Tian, Mengjian; Gao, Bingzhao
Highlights: Give a novel in-wheel powertrain system combined with dynamic vibration absorber. Uncouple the interaction between driving torque and mass block's travel. Offer sufficient gear ratio and mass block's travel range. Analyze ride comfort performance by using screw theory and Lagrange method. Abstract: Poor ride comfort is one of the drawbacks of in-wheel-drive electric vehicles (IWD-EVs). Structural schemes of the in-wheel powertrain system combining dynamic vibration absorber (IWP-DVA) can be applied to improve the ride comfort performance of the IWD-EVs without excessive useless weight. In this scheme, the in-wheel-drive motor is suspended as a mass block, thereby a dynamic vibration absorber (DVA) is mounted on the unsprung mass to absorb the vibration. This study developed a novel IWP-DVA involving a pair of symmetrical external-geared-slider-rocker (EGSR) mechanisms and a differential gear mechanism. In this paper, the novel IWP-DVA's effectiveness in preventing the driving torque and the mass block's travel from interacting was verified based on the static analysis of the single-EGSR mechanism, where the negative phenomena of stroke depletion due to the driving torque exists. For investigating the ride comfort responses and tuning the spring/damper parameters, a dynamics model of a quarter vehicle system equipped with the novel IWP-DVA was constructed by using screw theory and Lagrange method. After the selection of the DVA parameters, an analysis of the results of ride comfort tests showed that the novel IWP-DVA could improve the ride comfort with a sufficient stroke.